2010
DOI: 10.1080/07315724.2010.10719810
|View full text |Cite
|
Sign up to set email alerts
|

Age, Homocysteine, and Oxidative Stress: Relation to Hypertension and Type 2 Diabetes Mellitus

Abstract: Aging is accompanied by elevated homocysteine and oxidative stress levels similar to those observed in younger subjects with hypertension or diabetes mellitus, independent of age. Hence, these conditions appear to accelerate the age-dependent increase in homocysteine and oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 33 publications
3
33
1
Order By: Relevance
“…For the purpose of laboratory interpretation, it should be noted that total homocysteine levels increase with age and are lower in the pregnant population. 65,66 Genetic counseling should take into account the clinical reason for which the test was performed. Many studies have revealed discrepant findings between Caucasians and Asians.…”
Section: Acmg Practice Guidelinesmentioning
confidence: 99%
“…For the purpose of laboratory interpretation, it should be noted that total homocysteine levels increase with age and are lower in the pregnant population. 65,66 Genetic counseling should take into account the clinical reason for which the test was performed. Many studies have revealed discrepant findings between Caucasians and Asians.…”
Section: Acmg Practice Guidelinesmentioning
confidence: 99%
“…[8][9][10][11][12] Since both diseases are the primary clinical outcomes of metabolic syndrome, understanding of the cause of hyperhomocysteinemia may shed light on the etiology of metabolic syndrome. Plasma homocysteine levels are determined by three main factors: (1) the remethylation rate of homocysteine to methionine; (2) the conversion rate of homocysteine to cystathionine; and most importantly, (3) the amount of methylation of substrates.…”
Section: Methyl Consumers and Hyperhomocysteinemiamentioning
confidence: 99%
“…8,12 This phenomenon may reflect a difference in the compensatory capacity in the conversion of homocysteine to methionine or cystathionine, since plasma homocysteine levels are also found to go up with age. 9,38,39 Moreover, because the production of homocysteine is mainly determined by diet, 33 metabolic syndrome patients, even those with CVD, may have normal plasma homocysteine if they have shifted to a low methyl consumer diet and/ or have a higher capability to convert homocysteine to methionine (for example, due to folate supplementation) or to cystathionine. From this point of view, it seems that plasma homocysteine may not be a reliable indicator of the imbalance between methyl supply and consumption, especially in the early stage of metabolic syndrome.…”
Section: Pi+ Ppimentioning
confidence: 99%
See 1 more Smart Citation
“…Hcy levels can be reduced by folate administration while the production and effects of free radicals can be controlled by antioxidants. 11,12 In this study evaluation of oxidative stress level, antioxidant, homocysteine, and vitamin levels were measured in patients of diabetes mellitus type 2 at different time intervals.…”
mentioning
confidence: 99%